Comparison of the ABCD Score's Accuracy in Predicting Remission of Type 2 Diabetes Mellitus One Year After Sleeve Gastrectomy, One Anastomosis Gastric Bypass, and Sleeve Gastrectomy with Transit Bipartition - Kirkil, Cuneyt; Aydin, Ilayda; Yur, Mesut; Ag, Onur; Bozcan, Muhammed Yusuf (Springer, 2024)
Purpose ABCD score is one of the scoring systems that predicts the probability of T2DM remission after bariatric surgery. Its success in determining T2DM remission after sleeve gastrectomy with transit bipartition (TB) has not yet been validated. The aim of this study was to evaluate the predictive value of ABCD score in TB.Materials and Methods Of 438 patients with T2DM, 191 underwent sleeve gastrectomy (SG), 136 underwent one anastomosis gastric bypass (OAGB), and 111 underwent TB. Retrospective analysis of ABCD scores, 1-year postoperative remission rates, and the predictive accuracy of ABCD scores for these were conducted.Results In the SG, OAGB, and TB groups, respectively, median ABCD scores were 7, 6, and 4, while complete remission rates were 95.3%, 84.6%, and 76.6% (p < 0.001). The area under curves (AUCs) for SG, OAGB, and TB were 0.829 (95% CI = 0.768 to 0.879, p < 0.0001), 0.801 (95% CI = 0.724 to 0.865, p < 0.0001), and 0.840 (95% CI = 0.758 to 0.902, p < 0.0001), respectively. There was no statistically significant difference between AUCs.Conclusion ABCD score predicts the probability of remission at 1-year follow-up in T2DM patients undergoing TB as accurately as in patients receiving SG or OAGB.
Keywords: Type 2 diabetes mellitus; Remission; ABCD score; Transit bipartition